PENINGKATAN PENGETAHUAN KADER DALAM PEMANTAUAN TUMBUH KEMBANG BALITA - Dhiah Dwi Kusumawati; Rochany Septiyaningsih; Frisca Dewi Yunadi (LPPM STIKES Madani Yogyakarta, 2020)
Health Cadres are very important in society including monitoring the growth of Balita flowers through Posyandu. Lack of understanding and service skills, causing the cadre to become less self-sufficient and highly dependent on health and health care personnel. Therefore, at the time of services performed, the role of cadres often do not function properly. This activity aims to enhance the knowledge and skills of cadres in monitoring the growth of the Balita . The method used is counseling on the Growth of Flowers by involving students in the Al-Islamiyyah Cilacap Alert of Birth and evaluation using a question and answer instrument. The result of the devotional activity is that the cadre responds very enthusiastically to the counseling activity by showing the presence and enthusiasm of participating in the counseling event. There is an increase in the cadre's knowledge of monitoring the growing of Balita. The conclusion of the activity is that peer group counseling is easy to accept and enhances the cadre's knowledge of growing a Balita